2021
DOI: 10.1016/j.adaj.2020.09.022
|View full text |Cite|
|
Sign up to set email alerts
|

Dentists’ knowledge, attitudes, and professional behavior toward the COVID-19 pandemic

Abstract: Background COVID-19 continues to impact the dental community worldwide. The authors conducted a cross sectional electronic study to examine dentists’ knowledge, attitudes and professional behavior towards COVID-19 and the impact on their livelihood through a multi-site survey. Methods A questionnaire was circulated by electronic mail and social media platforms to dentists in North America, Europe, Eastern Mediterranean and Western Pacific regions. It covered demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 16 publications
3
53
0
2
Order By: Relevance
“…In addition, 86% of respondents reported a reduction in or closure of general anesthesia or deep sedation dental services. Likewise, in a questionnaire-based study to evaluate general dentists’ responses globally, most respondents (80%) also indicated that their workplaces were closed as a result of the COVID-19 outbreak [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 86% of respondents reported a reduction in or closure of general anesthesia or deep sedation dental services. Likewise, in a questionnaire-based study to evaluate general dentists’ responses globally, most respondents (80%) also indicated that their workplaces were closed as a result of the COVID-19 outbreak [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiological agent responsible for this outbreak was a new coronavirus (2019-nCoV) [2], which the International Committee on Taxonomy of Viruses labeled Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). On the 11 of February 2020, the World Health Organization (WHO) officially termed this new disease Coronavirus disease 2019 (COVID- 19) and only a month later declared the COVID-19 pandemic [3]. By the 9 of February 2021, the COVID-19 epidemic had spread to 255 countries and caused 106.1 million confirmed cases and over 2.3 million deaths, according to the WHO [4].…”
Section: Introductionmentioning
confidence: 99%
“…The resulting insights allow a deep understanding of barriers and enablers to implementation both on an emotional but also a factual level. Notably, our findings can be triangulated with those of quantitative evaluations (e.g., from surveys), which highlighted that knowledge on COVID-19 increased with time and was generally not the main barrier for ICM in more recent surveys; that the adoption of PPE varied widely and that some PPE, such as face shields and FFP2-masks, were not implemented regularly; that there was uncertainty regarding how to adapt practice infrastructure and organization to reduce infection risks and that, generally, the specific setting was associated with the implementation of measures [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Our study now adds insights as to why all these observations were made.…”
Section: Discussionmentioning
confidence: 99%
“…While the knowledge on COVID-19 has increased over the course of the pandemic, the majority of dentists have not yet implemented all recommended measures. A few dentists aimed to exceed recommendations or legal minimum standards [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. It is, however, not clear why implementation differs between measures, dentists and settings.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, around half of the participants accepted to treat patients with flu like symptoms and patients with known or suspected COVID-19 infection. Most of dentists from previous studies mainly conducted in the early period of the COVID-19 outbreak prefer not to treat patients with COVID-19 [ 18 , 22 , 27 , 28 ]. This was expected as many guidelines stated that only emergency interventions to be performed, with rescheduling of the elective treatment procedures [ 7 , 9 ].…”
Section: Discussionmentioning
confidence: 99%